Bi2S3 Nanorods Hosted on rGO Sheets from Pyrolysis of Molecular Precursors for Efficient Li‐Ion Storage. Issue 4 (8th November 2020) - Li, Zhongshuang; He, Mengmeng; Bo, Bing; Wei, Huijuan; Liu, Yanyan; Wen, Hao; Liu, Yushan; Zhang, Ke; Zhang, Panke; Li, Baojun
Abstract : Bismuth‐based compounds with high capacity and durability are still challenging in Li‐ion batteries (LIBs). In this article, Bi2 S3 nanorods hosted on reduced graphene oxide nanosheets (Bi2 S3 /rGO, BSG) are successfully prepared using molecular precursor pyrolysis strategy. 1D nanorod architecture possesses preeminent kinetic characteristics, shortening the ion diffusion path and increasing the contact area between electrode and electrolyte. The large specific surface area and charge polarization of rGO at the interface promote charge transfer. The capacity of material (BSG‐400) reaches 558.4 mAh g −1 at 0.2 A g −1 after 200 cycles. The anode properties of the composite outperform those of pristine Bi2 S3 . The introduction of graphene enables the interfacial interaction between rGO and Bi2 S3 . The closely contact interface improves the conductivity and lithium storage performances of Bi2 S3 . The regulatory effect of rGO on the electronic density of states and band gap of Bi2 S3 has been demonstrated by theoretical calculation. The synthetic approach has the advantages of universality, simple operation procedure, and strong repeatability. This research provides some ideas for the preparation of other metal sulfides/rGO nanomaterials and their application in battery research. Abstract : Bi2 S3 nanorods hosted on rGO nanosheets are prepared using a molecular precursor pyrolysis strategy. The strategy provides new ideas for preparation and applications of other metal compounds/carbon composite materials.